Point-of-Care Arterio-Venous Fistula Ultrasound in the Outpatient Hemodialysis Unit-A Survey on the Nurses' Perspective - Iulia Grosu; Oana Stirbu; Adalbert Schiller; Florica Gadalean; Flaviu Bob (MDPI AG, 2024)
The preservation of complication-free arterio-venous fistulas (AVF) for long-term hemodialysis (HD) use is associated with better overall patient outcomes, which is why this is a current goal in any HD center. Point-of-care ultrasound (POCUS) for in-center AVF assessment has proven its benefits in the identification of vascular access (VA) complications and as an additional tool to avoid blind cannulation. The current study aims to assess the change in the HD nurses' perceptions regarding AVF POCUS use in the HD center. The nursing staff anonymously answered a Likert scale questionnaire with five questions related to various aspects of AVF POCUS utility shortly after the technique had been implemented and at a 5-year follow-up. The results showed an overall positive attitude toward this method, both at implementation and at follow-up, with no statistically significant score changes for four out of the five items assessed. However, we found a statistically significant reduction in the nurses' cannulation confidence scores at the 5-year follow-up (p < 0.01). Overall, AVF POCUS implementation is regarded as a useful tool, with major benefits both for the patient and for the medical team. The current study results aim to support the introduction of AVF POCUS assessment as a standard practice from the nursing staff's viewpoint. This study was not registered.